Principal characteristics of patients acutely poisoned by ethanol in the region of Belgrade (Serbia) - Šegrt, Zoran; Vučinić, Slavica; Rančić, Nemanja; Vukčević-Perković, Nataša; Vuković-Ercegović, Gordana; Potrebić, Olivera; Kovačević, Aleksandra; Mijatović Jovin, Vesna; Jaćević, Vesna (Vojnosanitetski pregled, 2021)
Background/Aim. Acute intoxication by ethanol constitutes a significant part of the acute pathology caused by toxic chemicals, which require medical care in specialized health care institutions. The aim of the study was to determine some principal characteristics of the patients treated after acute ethanol poisoning, such as: participation in the total number of patients treated after acute poisoning by all chemical agents, age, sex, severity of poisoning and capacities for ambulatory or hospital treatment. Methods. A five-year retrospective case study was conducted on 20,891 acute poisoned patients, of which 10,731 were treated after acute ethanol poisoning during the period 2011–2015. All the subjects satisfied the diagnostic criteria of poisoning according to the World Health Organization International Classification of Diseases-10 and standardized Poison Severity Score scale. Results. Monitored parameters were analyzed in 10,731 patients acutely poisoned by ethanol, and their average number during one study year was 2146.2 ± 437.95. The average number of treated patients due to poisoning by ethanol (51.47 ± 2.86%) was statistically significantly higher than that of other causes of acute poisoning (p < 0.001). The majority of poisoned patients were men, aged 19 to 65 years, with mild to moderate symptoms of acute ethanol intoxication. The highest number of patients poisoned by ethanol had Poison Severity Score 1 (70.25 ± 5.04%, p < 0.001). Very few acute poisoned with ethanol required hospital treatment (1.05%). Anticipated number of patients acutely poisoned by ethanol had high percentage of increase for the period 2016–2020 (slightly more than 20%), which is worrying, primarily due to their high absolute number. Conclusion. Acute alcohol poisoning represents a significant part of the pathology in the total number of patients treated due to acute poisoning with various chemical substances. The results of this analysis showed that certain populations are particularly vulnerable to abuse of alcohol to the level requiring health care (male population, age 19˗65 years). Only a small number of patients (1% of all patients treated for acute alcohol poisoning) required clinical treatment. The obtained data provided the basis for a more targeted preventive action in certain population groups, as well as the adequate planning of professional medical staff engagement, material, spatial and other capacities. These data, also, provided the basis for additional detailed social, economic, health and other researches in this area as well as a more detailed registration of this type of poisoning and establishing a monitoring system and database.